Oncogenic PIK3CA induces centrosome amplification and tolerance to genome doubling. Issue 1 (December 2017) - Berenjeno, Inma; Piñeiro, Roberto; Castillo, Sandra; Pearce, Wayne; McGranahan, Nicholas; Dewhurst, Sally; Meniel, Valerie; Birkbak, Nicolai; Lau, Evelyn; Sansregret, Laurent; Morelli, Daniele; Kanu, Nnennaya; et al.
Abstract Mutations inPIK3CA are very frequent in cancer and lead to sustained PI3K pathway activation. The impact of acute expression of mutantPIK3CA during early stages of malignancy is unknown. Using a mouse model to activate thePik3ca H1047R hotspot mutation in the heterozygous state from its endogenous locus, we here report that mutantPik3ca induces centrosome amplification in cultured cells (through a pathway involving AKT, ROCK and CDK2/Cyclin E-nucleophosmin) and in mouse tissues, and increased in vitro cellular tolerance to spontaneous genome doubling. We also present evidence that the majority ofPIK3CA H1047R mutations in the TCGA breast cancer cohort precede genome doubling. These previously unappreciated roles ofPIK3CA mutation show that PI3K signalling can contribute to the generation of irreversible genomic changes in cancer. While this can limit the impact of PI3K-targeted therapies, these findings also open the opportunity for therapeutic approaches aimed at limiting tumour heterogeneity and evolution. Activated PI3K causes cancer, but the role of active PI3K mutations in early stages of malignancy are unclear. Here, the authors show in a mouse model that active PI3K induces centrosome amplification via AKT, ROCK, CDK2/Cyclin E and nucleophosmin, and increased tolerance of genome doubling.